Money Politics and Electoral Integrity in Local Democracy: A Case Study of Legislative Elections in Wajo Regency, South Sulawesi (2019–2024) - Jumardin Jumardin; Sunardi Purwanda; Elvi Susanti Syam; Bakhtiar Tijjang; Kairuddin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2026)
Background: Money politics remains one of the most persistent challenges undermining democratic consolidation in Indonesia, particularly at the local level where patron–client relationships and economic vulnerability converge. Despite the introduction of electoral reforms and stricter legal frameworks, vote buying continues to shape the outcomes of legislative elections across many regions . Purpose: This study investigates the dynamics of money politics in the legislative elections of Wajo Regency, South Sulawesi, focusing on the continuity and transformation of practices between the 2019 and 2024 electoral cycles. Employing a qualitative case study design, the research explores the socio-economic, cultural, and institutional factors that sustain transactional politics in local elections . Methods: Data were collected through in-depth interviews, participant observation, focus group discussions, and document analysis involving candidates, campaign teams, voters, government officials, and election observers. The analysis is guided by the theoretical frameworks of patron–client relations, rational choice theory, and system theory to explain how individual behavior, institutional weaknesses, and socio-cultural norms interact to normalize money politics . Originality: By situating Wajo as a microcosm of Indonesia’s broader electoral challenges, this study contributes to the understanding of how informal political economies persist within formal democratic institutions and provides insights for developing culturally grounded strategies to strengthen electoral integrity in local governance for the customary law. Even though the legal plurality of Indonesian society is directly protected by the constitution.